2014
DOI: 10.1103/physreva.89.013819
|View full text |Cite
|
Sign up to set email alerts
|

High-energy laser-pulse self-compression in short gas-filled fibers

Abstract: We examine the spatio-temporal compression of energetic femtosecond laser pules within short gas filled fibers. The study is undertaken using an advanced nonlinear pulse propagation model based on a multimode generalized nonlinear Schrödinger equation that has been modified to include plasma effects. Plasma defocusing and linear propagation effects are shown to be the dominant processes within a highly dynamical mechanism that enables 100 fs pulses to be compressed into the fewcycle regime after <50 mm of prop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
22
0

Year Published

2015
2015
2025
2025

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 37 publications
4
22
0
Order By: Relevance
“…Since the description of the propagation of the generating IR laser pulse and the harmonic radiation is full of twists and turns [24][25][26], i.e., Equations (1) and (5) suggest a complex intensity and wavelength dependence, the implementation of an evolutionary algorithm for finding the best suited pulse-shape is an established technique. (a) is a typical HHG spectrum from a hollow-core fiber with a pulse that is compressed by translating the prisms for highest XUV yield and using a flat mirror surface; (b) shows an optimization of the overall yield by adaptively shaping the deformable mirror.…”
Section: Tailored High-harmonic Generation In a Gas-filled Hcfmentioning
confidence: 99%
“…Since the description of the propagation of the generating IR laser pulse and the harmonic radiation is full of twists and turns [24][25][26], i.e., Equations (1) and (5) suggest a complex intensity and wavelength dependence, the implementation of an evolutionary algorithm for finding the best suited pulse-shape is an established technique. (a) is a typical HHG spectrum from a hollow-core fiber with a pulse that is compressed by translating the prisms for highest XUV yield and using a flat mirror surface; (b) shows an optimization of the overall yield by adaptively shaping the deformable mirror.…”
Section: Tailored High-harmonic Generation In a Gas-filled Hcfmentioning
confidence: 99%
“…The second mechanism may be called intrinsic, i.e., when fluctuations are rather based on highly nonlinear effects in the capillary such as associated with spatio-temporal reshaping of the drive laser pulse inside the capillary. It has recently been observed in an identical waveguiding capillary that such reshaping is related to beating of drive laser light propagating simultaneously in the fundamental and higher-order modes that are excited through ionization-induced scattering of the driving laser pulse [57,95] . Furthermore, the modeling in [95] showed that nonlinear optical effects like self-phase modulation or self-steepening do not significantly modify the pulse propagation in such a capillary.…”
Section: Methodsmentioning
confidence: 99%
“…It has recently been observed in an identical waveguiding capillary that such reshaping is related to beating of drive laser light propagating simultaneously in the fundamental and higher-order modes that are excited through ionization-induced scattering of the driving laser pulse [57,95] . Furthermore, the modeling in [95] showed that nonlinear optical effects like self-phase modulation or self-steepening do not significantly modify the pulse propagation in such a capillary. This is confirmed by calculating the characteristic propagation length required for these processes to become dominant [94].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations